Anatomy-morphological features of nasal mouth of ductus nasolacrimalis at pathological lacrimation - N. S. Tokareva; M. V. Shilov; A. V. Starokha; S. V. Logvinov (Бюллетень сибирской медицины, 2006)
Optical endoscopy of nasal cavities and general histological and histochemical methods were used to reveal that the anatomically adverse variants of the structure of nasal mouth of ductus nasolacrimalis against a background of the chronic catarrhal inflammation of a mucous membrane of lacrimal passages with abnormality of the mucociliary clearance in patients with pathological lacrimation promote the development of dacryostenoses.